1974
DOI: 10.1530/acta.0.0770527
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcaemia of Neoplasia, Parathyroid Hormone and Vitamin D: Studies in Parabiosis

Abstract: A localized transplantable Leydig cell tumour of the Fischer rat regularly produces lethal hypercalcaemia in thyroparathyroidectomized and intact hosts. The parabiosis model was used to explore and compare the hypercalcaemia producing action of this tumour, parathyroid hormone, and vitamin D. Administration of exogenous parathyroid hormone (10 and 20 units) to one thyroparathyroidectomized parabiont rat increased the serum calcium in both parabionts within 24 hours. Endogenous parathyroid hormone, studied by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The hypercalcemia in this model is associated with hypophosphatemia and renal phosphate wasting, as has been shown before [9][10][11]. In this study, we have found that the hypercalcemia is also associated with increased urinary cAMP excretion and low immunoreactive iPTH concentrations, also recently associated with the humoral Hypercalcemia of malignancy [7,19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The hypercalcemia in this model is associated with hypophosphatemia and renal phosphate wasting, as has been shown before [9][10][11]. In this study, we have found that the hypercalcemia is also associated with increased urinary cAMP excretion and low immunoreactive iPTH concentrations, also recently associated with the humoral Hypercalcemia of malignancy [7,19].…”
Section: Discussionsupporting
confidence: 83%
“…The tumors grown rapidly to a very large size but do not metastasize. Previous workers have shown that the hypercalcemia caused by these tumors is associated with hypercalciuria, phosphaturia, and hypophosphatemia [9][10][11]. In this study, we have further characterized this model and shown that it has the other features of the humoral hypercalcemia associated with human malignancies, including increased urinary cAMP excretion, renal phosphate wasting, and suppressed circulating iPTH concentrations.…”
Section: Summary a Transplantable Nonmetastasizingmentioning
confidence: 69%
See 1 more Smart Citation
“…However, in women, other osteolytic factors, possibly peptides, are also released in-vitro by human breast tumours. This factor may be related to the hypercalcaemic agent formed by an experimental rat Leydig cell tumour (ponthier and Rice, 1974).…”
Section: (B) Prostaglandinsmentioning
confidence: 99%
“…From exten sive studies, it can be said only that the hormone produced is probably not parathyroid hormone nor vitamin D or one of its metabolites [26], It is probably of small molecular weight and rapidly metabolized. …”
Section: Carcinoma Of the Ovarymentioning
confidence: 99%